2009
DOI: 10.1152/ajpcell.00052.2009
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the large-conductance background K+ channel in mouse B cells as TREK-2

Abstract: Mouse B cells and their cell line (WEHI-231) express large-conductance background K(+) channels (LK(bg)) that are activated by arachidonic acids, characteristics similar to TREK-2. However, there is no evidence to identify the molecular nature of LK(bg); some properties of LK(bg) were partly different from the reported results of TREK type channels. In this study, we compared the properties of cloned TREK-2 and LK(bg) in terms of their sensitivities to ATP, phosphatidylinositol 4,5-bisphosphate (PIP(2)), intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
23
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 30 publications
3
23
0
Order By: Relevance
“…Previously, we reported that mouse primary B lymphocytes and B cell lines (WEHI-231) express a large-conductance K2P-like K + channel, which was identified as TREK-2 based on the following properties: (1) high levels of unitary conductance (>200 pS), (2) activation by intracellular acidification, (3) activation by polyunsaturated fatty acids (e.g., arachidonic acid), (4) activation by membrane stretch, and (5) inhibition by small interfering RNA against TREK-2 (siTREK-2) [26,27,35,36]. In B cells, despite the significant density of functional TREK-2 activities measured under inside-out (i-o) patch clamp recordings (I TREK-2,i-o ), the TREK-2 current measured by whole-cell (w-c) patch clamp (I TREK-2,w-c ) with ATPcontaining pipette solution is very small.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we reported that mouse primary B lymphocytes and B cell lines (WEHI-231) express a large-conductance K2P-like K + channel, which was identified as TREK-2 based on the following properties: (1) high levels of unitary conductance (>200 pS), (2) activation by intracellular acidification, (3) activation by polyunsaturated fatty acids (e.g., arachidonic acid), (4) activation by membrane stretch, and (5) inhibition by small interfering RNA against TREK-2 (siTREK-2) [26,27,35,36]. In B cells, despite the significant density of functional TREK-2 activities measured under inside-out (i-o) patch clamp recordings (I TREK-2,i-o ), the TREK-2 current measured by whole-cell (w-c) patch clamp (I TREK-2,w-c ) with ATPcontaining pipette solution is very small.…”
Section: Introductionmentioning
confidence: 99%
“…In B cells, despite the significant density of functional TREK-2 activities measured under inside-out (i-o) patch clamp recordings (I TREK-2,i-o ), the TREK-2 current measured by whole-cell (w-c) patch clamp (I TREK-2,w-c ) with ATPcontaining pipette solution is very small. However, a dramatic spontaneous increase of I TREK-2,w-c is observed with ATP-free pipette solution [27,36]. Based on the prevention of ATPinduced I TREK-2,i-o suppression by PI-kinase inhibitors (wortmannin or LY29402) and the inhibition by PI(4,5)P 2 [16,27,36], we proposed that TREK-2 inhibition by intracellular ATP is mediated by membrane-delimited production of PI(4,5)P 2 .…”
Section: Introductionmentioning
confidence: 99%
“…by antigens (5), cleavage fragments of the third complement component (6), and bacterial, viral, or autoimmunity host DNA (7), and even certain chemokines (8). PLC␥ 2 activation results in InsP 3 -mediated increases in the concentration of free Ca 2ϩ , diacylglycerol-mediated activation of protein kinases C, and changes in transmembrane signaling directly mediated by PtdInsP 2 (9).…”
mentioning
confidence: 99%
“…Further to this publication, the LK bg background K ϩ channel of WEHI-231 cells was identified as TREK-2 but a role in B cell function has not been advanced (23). Work with human T cells purified from peripheral blood has shown the presence of TWIK-related acid-sensitive K ϩ channel 1 (TASK-1) and TASK-3, acid-sensitive and G q protein-regulated K 2P channels.…”
mentioning
confidence: 99%